An experimental study on performace of starch extracted from wheat flour as filtration control agent in drilling fluid - Raheel Iqbal; Fawad Pirzada; Muhammad Zubair; Ameer Mehmood (Institute of Advanced Engineering and Science, 2020)
The phenomenon of lost of mud filtrate into a porous permeable formation due to high hydrostatic pressure compared to the formation pressure is known as fluid loss. This cause some major problems in well during drilling as poor cementing job, pipe stuck, and formation damage. Thus, to safe the well from such problems and in order to make safe and effective drilling an additive from wheat flour is extracted which is starch, and acting as a fluid loss control agent. The purpose of this research is to investigate the potential of utilizing this additive to form environmentally safe, non-toxic, high biodegradability and low-cost water-based drilling fluid samples with varying the amount of starch. Experimental results showed that Efficiency of starch obtained from wheat-flour is showing increment in rheological properties as compare to starch present in market by using same and varying quantity of both and observed that wheat-flour starch is more efficient as compare to starch in market. On the other hand, the efficiency of starch is good but it has been also improved by the extraction of starch from wheat-flour by the centrifugation process.